Pengobatan Tradisional untuk Ibu dan Bayi Pasca Melahirkan pada Masyarakat Kota Semarang - Islamy, Cindy Fa'era; Husain, Fadly (Universitas Lambung Mangkurat, 2026)
Traditional medicine is a cultural heritage that has been used for generations by the people of Genuk District, Semarang City. The people of Semarang City still maintain traditional medicine practices, one of which is the tradition of traditional medicine for mothers and babies after childbirth. The persistence of this traditional medicine practice is based on the fact that the postpartum phase is a crucial phase for mothers and babies. In addition to being considered to have fewer side effects than modern medicine, traditional medicine also reflects respect for local traditions in the community. This study aims to describe the classification of